KEMAMPANAN SEKURITI MAKANAN DALAM ERA PERINDUSTRIAN: PENGAJARAN DARIPADA MALAYSIA - Zahrul Akmal Damin; Ahmad Martadha Mohamed (Journal of Techno-Social, 2015)
In Malaysia, the development of agriculture for food security is emphasized to ensure a stable supply in balancing the domestic demand. In order to achieve this goal, the government has emphasized the agricultural development policy despite the challenges of rapid industrial sector. Since 1984, the challenge of agricultural development for food security is critical when Malaysia experienced a phase of active industrial development. Thus in the context of the framework, this study is to see agricultural development efforts being undertaken by government leaders to ensure food security in the industrial era is guaranteed. Based on the five-year development plan of Malaysia, the government's strategies to provide sustainable food production are examined in details. By using the qualitative analysis, this paper analyzes the policies of the government leaders regarding the development of agriculture for food security which includes (i) the administration phase of Tun Dr. Mahathir Mohamad, (ii) the administration phase of Tun Abdullah Ahmad Badawi, and (iii) the administration phase of Dato 'Seri Mohd. Najib Abdul Razak. It is hoped that the findings will help the policymakers in formulating the agricultural development for food security in order to optimize the food production and at the same time can protect the country from threats that could disrupt the stability of the country due to the lack of supply.